Review of Telemedicine and E-health: A bibliometric analysis - Anuj Kumar; Sangeet Kaur Sandhu; Geetika Madaan; Nimit Gupta; Shafique Ahmed (ACHSM, 2023)
The fields of telemedicine and e-health have grown in recent years due to advancements in technology and wearable devices. This research aimed to look back at the last 27 years of e-health and telemedicine studies to see how they've evolved. Article details for the selected papers were obtained from the Scopus database. Article details for the selected papers were retrieved using the Scopus database. Insights from the existing study suggest an upward trend in the number of publications and a peculiar pattern in the distribution of both authors and articles. Nine of the most influential researchers and the most often cited works were identified. VOS viewer software underwent keyword, author, and country co-occurrence analyses, as well as co-authorship analysis. According to a country-by-country research review, the United States, Italy, and Germany are the top three countries in article production in telemedicine and electronic health. Doarn (8 publications), Merrell R.C. (7 publications), Giansanti D. (7 publications), and Maccioni G (4 publications) were found to be the most prolific authors in the field of telemedicine and e-health. The study used bibliometric analysis to determine that the keywords "telemedicine," "human," and "e-health" were the most frequently used in the 69 publications chosen for the study. This study is useful for telemedicine and e-health since it provides a thorough understanding of the literature in these subjects, highlighting the most studied and understudied areas from which to launch future research endeavours.